Reproductive biology of cassava = Biología reproductiva de la yuca - Ceballos, Hernán; Morante, Nelson; Pineda, Lizzeth Marcela; Bolaños, Eugenio (International Center for Tropical Agriculture, 2018)
This 9-minute video presents images of cassava flowering and its close association with branching. Changes in the shape of the apical meristem before emergence of flowers, female and male flowers and pollination techniques are described in detail. Este video de 9 minutos muestra los eventos más relevantes en la floración de la yuca/mandioca y su asociación con la ramificación. Se muestran los cambios en la forma del ápice de crecimiento previos a la emergencia de inflorescencias, las flores femeninas y masculinas y el protocolo para realizar cruzamientos dirigidos.